2007
DOI: 10.1038/nm1534
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular carbonic anhydrase mediates hemorrhagic retinal and cerebral vascular permeability through prekallikrein activation

Abstract: Excessive retinal vascular permeability contributes to the pathogenesis of proliferative diabetic retinopathy and diabetic macular edema, leading causes of vision loss in working-age adults. Using mass spectroscopy-based proteomics, we detected 117 proteins in human vitreous and elevated levels of extracellular carbonic anhydrase-I (CA-I) in vitreous from individuals with diabetic retinopathy, suggesting that retinal hemorrhage and erythrocyte lysis contribute to the diabetic vitreous proteome. Intravitreous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
329
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(359 citation statements)
references
References 43 publications
19
329
1
1
Order By: Relevance
“…Carbonic anhydrase (CA) has been identified by proteomic analysis in the vitreous humour from PDR patients; CA production was increased in the vitreous of diabetic retinopathy patients compared with the controls [7,8]. In this study, we have confirmed this finding.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Carbonic anhydrase (CA) has been identified by proteomic analysis in the vitreous humour from PDR patients; CA production was increased in the vitreous of diabetic retinopathy patients compared with the controls [7,8]. In this study, we have confirmed this finding.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, we have confirmed this finding. The presence of CA was initially thought to be due to retinal haemorrhage and erythrolysis, but subsequent investigation demonstrated that CA is also actively involved in the progression of diabetic retinopathy; CA-1 expression leads to the activation of the contact system, the intrinsic pathway of coagulation, and promotes retinal vessel leakage and intraretinal edema via increased kallikrein activity [8]. The mechanisms involved in the increasing production of CA and the value of CA to potential therapeutic targets require further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La rétinopathie proliférative diabétique (RD) et la réti-nopathie du prématuré (RP) en sont malheureusement des exemples fréquents et représentent les deux principales causes de cécité chez les personnes de moins de cinquante ans dans les pays industrialisés [2,3]. Ces pathologies sont caractéri-sées par une croissance vasculaire anormale et excessive pouvant aller, selon la sévérité, jusqu'au détachement rétinien.…”
Section: Les Rétinopathies Ischémiques Prolifératives Et L'angiogenèseunclassified
“…Although this could imply that blood itself has no detrimental effects on neuronal tissue, several studies suggest intravascular coagulation and effects of blood constituents as trigger mechanisms, which may worsen outcome after ASDH (Jenkins et al, 1990;Karabiyikoglu et al, 2005;Lee et al, 1997;Stein et al, 2002). For instance, injection of thrombin into the striatum is neurotoxic (Fujimoto et al, 2006), injections of blood or blood lysate affect blood-brain barrier integrity (Gao et al, 2007;Power et al, 2003), and contact of blood with brain tissue causes inflammation (Lee et al, 2006). Furthermore, superfusion of rat cortex with hemoglobin or products from hemolysis can induce cortical spreading depolarization and spreading ischemia with neuronal cell death (for definitions see secton Discussion and references Dreier et al, 1998Dreier et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%